Property Title, Formal Credit Access and Business Expansion - Okon, Emmanuel O. (International Journal of Marketing Research Innovation, 2018)
The cardinal objective of this study is to examine the impact of Land Title Document on credit access and business growth. A case study was applied on Nasarawa state, Nigeria to better understand the phenomenon been researched. Information was gathered from the field through face-to-face interviews and through the administering of questionnaire among business operators in some selected towns. The research revealed that a large proportion of respondents do not have Land Title Document to their business premises and that they have never made a request for it from government agency before. 60.00% of respondents’ responded that the duration of the processing of the document takes months/years. 44.52% of respondents reported that never have banks made request for the document before granting loan facilities while 30.24% of respondents’ indicated ‘yes, often’. From the responses, 40.47% of respondents were of the view that possession of ‘C of O’ document will not enhance their capital based and business expansion. The views of the respondents suggest that delay is a major problem in the processing of Land Title Document. Among the reasons cited for the delays are problems with documentation and legal issues. A reasonable percentage of respondents (31.43%) were of the view that the cost of obtaining ‘C of C’ is high and difficult in the State. A suggested solution is that the government agency handling this document should be reorganize and the steps required to obtain this document should be reduced and made uniform within the State.